Climate in 14th-Century England: Catastrophic Change, Social Strategies and the Origins of Capitalism - Daniel Ribera Vainfas (Social Sciences)
This work aims to explore climate change as a decisive element for the transition from feudalism toward capitalism and considers the Marxist transition debate as a framework. In order to avoid the deterministic trap, climate must be considered as a condition framing the historical possibilities in a dialectical relationship with human historical agents. Thus, this paper explores the interactions between medieval English society, focusing on land use and class relation, and the conditions imposed by nature, particularly the change in rainfall and the transformation of ecological conditions around the North Sea Basin, especially on England’s east coast. Through the course of this research, we found out that the climate change that happened in the 14th century is one important condition for the rise of capitalism, as it creates certain pressures on both peasant and manorial economies that exacerbate their contradictions and sets a course for profound societal change.